Penerapan Budaya Positif Untuk Mewujudkan Karakter Profil Pelajar Pancasila dalam Kurikulum Merdeka - Purwati; Aiman Faiz; Nur Laeli Asifah; Anggra Oktaviani; Widianingsih; Pipih Hadistia; Azhar Saifullah Hafidz (Attractive : Innovative Education Journal, 2024)
The research discusses the importance of character education in facing the era of globalization where foreign cultures easily influence Indonesian culture. Various aspects of life, including culture can also change due to the flow of negative information by integrating Pancasila values in education. Education has a crucial role in shaping the character of students as the nation's successor. School culture, as a result of long-term learning experiences, can influence the attitudes and behaviors of school members. Character education aims to teach positive habits to individuals so that they can behave in accordance with the values that shape their personality. This research uses qualitative methods with data collection techniques through observation, interviews, and documentation at SD Negeri Bima. The research subjects included teachers and students. The results showed that the formation of a positive culture at school was carried out through class agreements, habituation every morning, and the application of positive culture in learning. A supportive school environment, open communication with parents, and control of students' social-emotional well-being are also important in shaping students' character. The implementation of character education varies from country to country, but the formation of national character is considered a fundamental need. Educational institutions play an important role in strengthening the character building process, and the school curriculum should reflect the desired character values. Through various practices and active involvement, schools can shape students' character effectively and holistically.